ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN DI PROVINSI SUMATERA UTARA TAHUN 1978-2014 DENGAN METODE ORDINARY LEAST SQUARE - N D Isnayanti; Arnah . Ritonga (KARISMATIKA: Kumpulan Artikel Ilmiah, Informatika, Statistik, Matematika dan Aplikasi, 2017)
AbstractThe purpose of this study was to analyze the factors affecting the level of unemployment in the province of North Sumatra in 1978-2014. With independent variable population of the workforce, inflation, economic growth, minimum wage and the level of upper secondary education graduates in the province of North Sumatra, while the dependent variable is unemployment. The data used are secondary data from the Central Statistics Agency (BPS) of North Sumatra province with time series from 1978 to 2014 year. Research steps to be performed are: Determine the theory or hypothesis; Creating mathematical models and econometric model of hypotheses; Collecting data; Parameter estimation of an econometric model; Test hypotheses; and make conclusions. The analytical method used was Ordinary Least Square method or the method of least squares. Data analysis technique used is multiple linear regression using Eviews program 7. The results showed that the variables of the labor force has positive effect amounting to 3 059 904% and not significant, positive bepengaruh inflation at 0, 020 060% and not significant, negative impact of economic growth 3 105 293% and a significant, negative impact of minimum wage amounted to 1, 003 877% and a significant and positive influence education levels of 0, 282 733% and significant impact on the unemployment rate in the province of north Sumatra in 1978-2014. The most dominant factor affecting the level of unemployment in the province of North Sumatra in 1978 2014 in this study is a factor of economic growth.Keywords : Labor Force, Inflation, Ordinary Least Square method, Unemployment, Economic Growth, Education Level, Minimum Wage